Ferromanganese composite catalyst and preparation method thereof, oxidation reaction device and water treatment equipment

By preparing nitrogen-doped graphene-coated ferromanganese composite catalyst, the problem of traditional water treatment technology's poor bisphenol A removal effect and difficulty in activation of the advanced oxidation method of persulfate is solved, and efficient and stable bisphenol A removal is achieved, reducing the treatment cost.

CN119702041APending Publication Date: 2025-03-28长江三峡(海南)绿色发展投资有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411898685.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional water treatment technology does not have the effect of removing bisphenol A, and advanced persulfate oxidation method is difficult to activate under mild conditions, and metal ion catalysts are prone to deactivate, which limits large-scale applications.

Method used

Using a ferromanganese composite catalyst, a combination of K3[Fe(CN)6], Mn(NO3)2, polyvinylpyrrolidone and deionized water was prepared to form a nitrogen-doped graphene-coated ferromanganese composite catalyst to improve catalytic activity and stability.

Benefits of technology

It improves the activity and service life of the catalyst, reduces the treatment cost, and is suitable for large-scale application in the treatment of bisphenol A in water in advanced oxidation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702041A_ABST
    Figure CN119702041A_ABST
Patent Text Reader

Abstract

The invention discloses a ferromanganese composite catalyst and a preparation method thereof, an oxidation reaction device and water treatment equipment. The ferromanganese composite catalyst is prepared from the following raw materials: K3 [Fe (CN) 6], Mn (NO3) 2, polyvinylpyrrolidone and deionized water. The ratio of the K3 [Fe (CN) 6] to the Mn (NO3) 2 to the polyvinylpyrrolidone is (0.005 to 0.015 mol): (0.005 to 0.015 mol): (1.5 to 5.0 g): (100 to 500 ml). The preparation method comprises the following steps: (1) mixing K3 [Fe (CN) 6], Mn (NO3) 2 and polyvinylpyrrolidone with deionized water, and stirring to obtain a precipitate; (2) washing and drying the precipitate in the step (1) to obtain a ferromanganese precursor material; and (3) calcining the ferromanganese precursor material in the step (2) in N2 atmosphere to obtain the ferromanganese composite catalyst. The prepared ferromanganese composite catalyst is high in catalytic activity, the service life of the ferromanganese composite catalyst is prolonged, the requirement for frequent replacement of the catalyst is reduced, the treatment cost is reduced, and large-scale application of bisphenol A in water treated through a persulfate advanced oxidation method is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of pollution control, and in particular to a manganese-iron composite catalyst and a preparation method thereof, an oxidation reaction device and water treatment equipment. Background Art

[0002] Bisphenol A (BPA) is a chemical widely used in plastic products and epoxy resins. The ubiquity of BPA in daily life not only poses a threat to human health, but may also have long-term effects on aquatic organisms. Traditional water treatment technologies, such as biodegradation, adsorption and chemical precipitation, are not ideal for removing BPA.

[0003] The existing technology uses persulfate-based advanced oxidation processes (PS-AOPs) to treat bisphenol A in water, by activating persulfate (such as sodium persulfate or potassium persulfate) to produce highly active sulfate radicals. These free radicals have extremely strong oxidizing ability and can effectively degrade pollutants such as bisphenol A in water.

[0004] However, the activation process of persulfate often requires high activation energy, which limits its application under mild conditions. In the process of using traditional metal ion catalysts to catalyze the persulfate reaction to treat bisphenol A, the metal ion catalyst is easily deactivated, which limits the large-scale application of persulfate advanced oxidation method to treat bisphenol A in water. Summary of the invention

[0005] In view of this, the present invention proposes a manganese-iron composite catalyst and a preparation method thereof, an oxidation reaction device and a water treatment equipment to solve the above problems.

[0006] The technical solution of the present invention is achieved in this way:

[0007] A manganese-iron composite catalyst is prepared from the following raw materials: K3[Fe(CN)6], Mn(NO3)2, polyvinyl pyrrolidone and deionized water.

[0008] The ferromanganese composite catalyst prepared by the invention has high catalytic activity, prolongs the service life of the ferromanganese composite catalyst, reduces the need for frequent catalyst replacement, reduces treatment costs, and is conducive to large-scale application of persulfate advanced oxidation method to treat bisphenol A in water.

[0009] Furthermore, the ratio of K3[Fe(CN)6], Mn(NO3)2 and polyvinyl pyrrolidone is: 0.005-0.015 mol: 0.005-0.015 mol: 1.5-5.0 g: 100-500 ml.

[0010] Furthermore, the molar ratio of K3[Fe(CN)6] and Mn(NO3)2 is 0.9-1.1:0.9-1.1.

[0011] The present invention also provides a method for preparing a manganese-iron composite catalyst, comprising the following steps:

[0012] (1) K3[Fe(CN)6], Mn(NO3)2 and polyvinyl pyrrolidone are mixed with deionized water and stirred to obtain a precipitate;

[0013] (2) washing and drying the precipitate from step (1) to obtain a ferromanganese precursor material;

[0014] (3) Calcine the ferromanganese precursor material in step (2) under a N2 atmosphere to obtain a ferromanganese composite catalyst.

[0015] Furthermore, in step (1), the stirring time is 30 to 60 minutes.

[0016] Furthermore, in step (2), the drying temperature is 60 to 80° C. and the drying time is 18 to 36 hours.

[0017] Furthermore, in step (3), the calcination temperature is 600-800° C., the calcination time is 2-3 h, and the heating rate is 5-10° C. / min.

[0018] An oxidation reaction device comprises a reaction tube, wherein a reaction chamber is defined in the reaction tube, wherein the reaction chamber comprises a first packing layer, a second packing layer and a third packing layer arranged from bottom to top along the height direction, wherein the second packing layer contains any manganese-iron composite catalyst described in any one of the present invention.

[0019] Furthermore, the first packing layer, the second packing layer and the third packing layer all contain quartz sand; the bottom end of the reaction cylinder is provided with a water inlet, and the top end of the reaction cylinder is provided with a water outlet and an exhaust port.

[0020] A water treatment device comprises a water tank, a water pump, a dosing box, a dosing pump and an oxidation reaction device as described in any one of the present invention; the water tank is used to supply water to the oxidation reaction device; the water inlet end of the water pump is connected to the water tank, and the water outlet end of the water pump is connected to the water inlet of the oxidation reaction device; the dosing box is used to provide oxidant to the oxidation reaction device; the input end of the dosing pump is connected to the dosing box, and the output end of the dosing pump is connected to the oxidation reaction device.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The preparation method, oxidation reaction device and water treatment equipment of the manganese-iron composite catalyst provided by the present invention, wherein the manganese-iron composite catalyst coated with nitrogen-doped graphene is prepared by the preparation method of the present invention, and the doping of nitrogen atoms can introduce additional active sites and change the electronic structure of graphene, thereby playing the effect of improving the activity of the catalyst, and in addition, the synergistic effect of manganese and iron can also provide more active sites, thereby improving the catalytic efficiency. The coating of graphene can effectively prevent the aggregation and sintering of metal nanoparticles of manganese and iron, thereby improving the thermal stability and chemical stability of the prepared manganese-iron composite catalyst, and then effectively reducing the problem of deactivation of the manganese-iron composite catalyst during the oxidation reaction. Nitrogen-doped graphene has good electrical conductivity, which is conducive to improving the electron transfer rate, thereby enhancing the reaction rate of the catalytic reaction. In addition, the use of relatively cheap and environmentally friendly metals such as iron and manganese is conducive to reducing the cost of the catalyst and the impact on the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 TEM image of the ferromanganese composite catalyst prepared by the preparation method of the ferromanganese composite catalyst according to an embodiment of the present invention;

[0024] Figure 2 The XRD image of the ferromanganese composite catalyst prepared by the preparation method of the ferromanganese composite catalyst according to an embodiment of the present invention;

[0025] Figure 3 It is a structural schematic diagram of a water treatment device according to an embodiment of the present invention;

[0026] Figure 4 This is a performance characterization diagram of the water treatment equipment according to an embodiment of the present invention for activating persulfate to continuously degrade bisphenol A;

[0027] Figure 5 This is a graph showing changes in metal dissolution concentration during the persulfate oxidation reaction activated by the water treatment equipment according to an embodiment of the present invention.

[0028] In the figure: 100 - oxidation reaction device; 110 - reaction tube; 111 - first packing layer; 112 - second packing layer; 113 - third packing layer; 114 - water inlet; 115 - water outlet; 116 - exhaust port;

[0029] 200-water treatment equipment; 210-water tank; 220-water pump; 230-dosing box; 240-dosing pump. DETAILED DESCRIPTION

[0030] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0031] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0032] The prior art uses a persulfate advanced oxidation process to treat bisphenol A in water. The activation process of persulfate often requires a high activation energy, which limits its application under mild conditions. The traditional metal ion catalyst is easily deactivated during the persulfate reaction to treat bisphenol A, which limits the large-scale application of the persulfate advanced oxidation process to treat bisphenol A in water.

[0033] In view of this, the present invention provides a method for preparing a ferromanganese composite catalyst, an oxidation reaction device and water treatment equipment. The ferromanganese composite catalyst prepared by the method for preparing the ferromanganese composite catalyst has high catalytic activity, prolongs the service life of the ferromanganese composite catalyst, reduces the need for frequent replacement of the catalyst, reduces the treatment cost, and is conducive to the large-scale application of persulfate advanced oxidation method to treat bisphenol A in water.

[0034] Example 1

[0035] A method for preparing a manganese-iron composite catalyst comprises the following steps:

[0036] S101, mixing K3[Fe(CN)6], Mn(NO3)2 and polyvinyl pyrrolidone with deionized water, stirring, and obtaining a precipitate;

[0037] The precipitate of the composite material containing manganese and iron is obtained through step S101, wherein the polyvinyl pyrrolidone (PVP) solid powder is used as a stabilizer and dispersant to improve the stability and dispersibility of the precipitate and prevent particle agglomeration. In addition, PVP is also used as a surfactant to control the growth of particles, thereby obtaining nano-scale or micro-scale particles, so that the precipitate of the composite material containing manganese and iron has sufficient active sites, so as to improve the catalytic efficiency of the composite material when used as a catalyst.

[0038] S102, washing and drying the precipitate obtained in step S101 to obtain a ferromanganese precursor material;

[0039] S103, calcining the ferromanganese precursor material in step S102 under a N2 atmosphere to obtain a ferromanganese composite catalyst.

[0040] During the calcination process of step S103, polyvinyl pyrrolidone may be carbonized to form a carbon base. By calcining the ferromanganese precursor material under a N2 atmosphere, nitrogen atoms are introduced into the ferromanganese precursor material to form a nitrogen-doped graphene-like structure, which is beneficial to improving the activity of the ferromanganese composite catalyst, thereby improving the catalytic efficiency.

[0041] The preparation method of the ferromanganese composite catalyst of the present invention is to prepare the ferromanganese composite catalyst coated with nitrogen-doped graphene by the preparation method of the ferromanganese composite catalyst, the doping of nitrogen atoms introduces additional active sites, and changes the electronic structure of graphene, thereby playing the effect of improving the activity of the catalyst, in addition, the synergistic effect of manganese and iron can also provide more active sites, thereby improving the catalytic efficiency. The coating of graphene can effectively prevent the aggregation and sintering of the metal nanoparticles of manganese and iron, thereby improving the thermal stability and chemical stability of the prepared ferromanganese composite catalyst, and then effectively reducing the problem of deactivation of the ferromanganese composite catalyst during the oxidation reaction. Nitrogen-doped graphene has good electrical conductivity, is conducive to improving the electron transfer rate, thereby enhancing the reaction rate of the catalytic reaction. In addition, relatively cheap and environmentally friendly metals such as iron and manganese are used, which is conducive to reducing the cost of the catalyst and the impact on the environment.

[0042] In some embodiments, the molar ratio of K3[Fe(CN)6] and Mn(NO3)2 is 1:1, which is beneficial to uniformly distribute iron and manganese in the product, thereby forming a uniform bimetallic nanostructure, which is beneficial to improving the catalytic performance of the final product (manganese-iron composite catalyst).

[0043] The molar amounts of K3[Fe(CN)6] and Mn(NO3)2 are both 0.005-0.015 mol. In some embodiments, the molar amounts of K3[Fe(CN)6] and Mn(NO3)2 are 0.005 mol, 0.007 mol, 0.009 mol, 0.011 mol, 0.013 mol or 0.015 mol. The molar amounts of K3[Fe(CN)6] and Mn(NO3)2 are both controlled within the range of 0.005-0.015 mol, so that the concentration of the reactants is low, which helps to reduce the particle size of the product, thereby increasing the specific surface area of ​​the produced ferromanganese composite catalyst, providing more active sites, and thus improving the catalytic activity of the ferromanganese composite catalyst.

[0044] The mass of polyvinyl pyrrolidone is 1.5 to 5.0 g. In some embodiments, the mass of polyvinyl pyrrolidone is 1.5 g, 2 g, 2.5 g, 3 g, 3.5 g, 4.0 g, 4.5 g or 5.0 g.

[0045] Polyvinyl pyrrolidone can be used as a stabilizer to effectively prevent the agglomeration of nanoparticles during the synthesis process. In the mass range of 1.5 to 5.0 g, polyvinyl pyrrolidone can provide sufficient coverage and protection for the particles, so that the particles remain dispersed, thereby improving the uniformity and stability of the material. In addition, the use of polyvinyl pyrrolidone can also promote the carbonization process of the ferromanganese precursor material. During the high-temperature calcination process, polyvinyl pyrrolidone can also be used as a carbon source to promote the carbonization process, forming a carbon coating layer or a carbon-based structure outside the ferromanganese precursor material, which is beneficial to improve the structural stability of the ferromanganese composite catalyst.

[0046] The volume of deionized water is 100 to 500 ml. In some embodiments, the volume of deionized water is 100 ml, 150 ml, 200 ml, 250 ml, 300 ml, 400 ml or 500 ml. An appropriate amount of deionized water can ensure that K3[Fe(CN)6], Mn(NO3)2 and polyvinyl pyrrolidone are fully dissolved, thereby promoting uniform mixing of the components and facilitating uniform distribution of the components in the precipitate.

[0047] In some embodiments, the stirring time of step S101 is 30 to 60 minutes, and in some embodiments, the stirring time is 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes. By stirring for 30 to 60 minutes, it is beneficial to fully dissolve and mix K3[Fe(CN)6], Mn(NO3)2 and polyvinyl pyrrolidone solid powder, so that each component in the precipitate formed in step (1) is evenly distributed, which is beneficial to improve the uniformity and activation performance of the manganese-iron composite catalyst finally formed. Further, by controlling the duration of stirring, it is beneficial to control the growth process of the particles of the precipitate of step (1) to form nano-scale particles, thereby increasing the specific surface area and active sites of the particles, and then improving the activation performance of the iron-manganese composite catalyst finally generated.

[0048] In some embodiments, the drying temperature in step S102 is 60° C. to 80° C., and in some embodiments, the drying temperature is 60° C., 65° C., 70° C., 75° C. or 80° C. The drying condition of 60° C. to 80° C. is relatively mild, which can ensure effective removal of moisture in the precipitate on the one hand, and on the other hand, is also conducive to avoiding damage to the structure of the precipitate by high temperature, thereby improving the structural stability of the generated ferromanganese precursor material.

[0049] The drying time in step S102 is 18 to 36 hours. In some embodiments, the drying time is 18 hours, 21 hours, 24 hours, 27 hours, 30 hours, 33 hours or 36 hours.

[0050] By drying the precipitate at 60°C to 80°C for 18 to 36 hours, it is ensured that the moisture in the precipitate is fully removed to avoid uneven structure due to the moisture in the precipitate during the subsequent calcination process, or to avoid the side reaction leading to the reduction of the ferromanganese composite catalyst and the introduction of impurities. In addition, the mild drying temperature and the long drying time can make the precipitate dry slowly and fully, which is conducive to reducing the internal stress of the material, thereby improving the structural stability of the ferromanganese precursor material.

[0051] In some embodiments, when the ferromanganese precursor material is calcined under a N2 atmosphere, the calcination temperature of step S103 is 600-800°C. In some embodiments, the calcination temperature is 600°C, 650°C, 700°C, 750°C or 800°C. In the temperature range of 600-800°C, the ferromanganese precursor material may undergo phase transition and crystallization, which helps to form a ferromanganese composite catalyst with a good crystal structure and improve the catalytic performance of the ferromanganese composite catalyst. In addition, the calcination temperature of 600-800°C can also ensure the structural stability of the ferromanganese precursor material and avoid excessive grain growth or sintering caused by high temperature.

[0052] The heating rate of step S103 is 5 to 10°C / min. In some embodiments, the heating rate is 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min. The heating rate of 5 to 10°C / min is conducive to controlling the growth rate of the particles, so that the ferromanganese composite catalyst forms small and uniform particles to increase the specific surface area of ​​the ferromanganese composite catalyst. By controlling the heating rate, the thermal stress inside the ferromanganese precursor material can be reduced, and cracks and defects in the generated ferromanganese composite catalyst can be avoided. In addition, by controlling the heating rate, the phase change and chemical reaction process of the ferromanganese precursor material can also be optimized to ensure the formation of the required crystal phase and chemical components.

[0053] The calcination time in step S103 is 2 to 3 hours. In some embodiments, the third preset time is 2 hours, 2.5 hours or 3 hours. The third preset time is 2 to 3 hours to ensure the full reaction and crystallization of the ferromanganese precursor material, thereby improving the mechanical stability and chemical stability of the ferromanganese composite catalyst.

[0054] One of the specific embodiments of the preparation process of the ferromanganese composite catalyst is introduced below:

[0055] (1) At room temperature, 0.015 mol of K3[Fe(CN)6], 0.015 mol of Mn(NO3)2, and 4.0 g of polyvinyl pyrrolidone solid powder were placed in 300 mL of deionized water and magnetically stirred for 45 min to obtain a precipitate;

[0056] (2) Washing and centrifuging the precipitate from step (1) and placing it in a forced air drying oven, drying it at 80° C. for 24 h, to obtain a ferromanganese precursor material.

[0057] (3) The ferromanganese precursor material of step (2) is heated to 700° C. at a heating rate of 5° C. / min under a N2 atmosphere and calcined for 2 h. After calcination, the material is naturally cooled to room temperature to obtain a ferromanganese composite catalyst.

[0058] The prepared manganese-iron composite catalyst was characterized by transmission electron microscopy (TEM). Figure 1 . It can be seen that the manganese-iron composite catalyst of the present embodiment shows a porous microsphere morphology, which can increase the specific surface area of ​​the material, and is conducive to exposing the surface active sites of the manganese-iron composite catalyst, thereby improving the catalytic effect on the persulfate oxidation reaction. At the same time, it can also be seen that the manganese-iron composite catalyst is composed of a large amount of metal crystal nanoparticles and carbon nanotubes, and the metal crystals are tightly wrapped by nitrogen-doped graphene to form a core-shell structure. This structure helps to improve the stability of the manganese-iron composite catalyst, and can prevent the aggregation and peeling of metal nanoparticles, thereby extending the service life of the manganese-iron composite catalyst. In addition, the lattice fringes of different crystal phases in the manganese-iron composite catalyst confirm the clarity and orderliness of its crystal structure, and the orderly atomic arrangement can provide more active sites and better electron transmission paths, which is conducive to improving the catalytic efficiency of the manganese-iron composite catalyst.

[0059] Furthermore, the above-mentioned manganese-iron composite catalyst was characterized by XRD, and the results are shown in Figure 2 , it can be seen that the manganese-iron composite catalyst has crystal structure characteristics such as MnFe2O4, Fe2N, Fe5C2, Mn5C2 and nitrogen-doped carbon nanotubes. It can be seen that there may be a synergistic effect between different crystal phases, which is beneficial to improve the catalytic performance of the manganese-iron composite catalyst. At the same time, the multiphase composite material can improve the mechanical strength and chemical stability of the manganese-iron composite catalyst because different phases complement each other.

[0060] Example 2

[0061] See also Figure 3 An oxidation reaction device 100 includes: a reaction tube 110, the reaction tube 110 defines a reaction chamber, and the reaction chamber has a first packing layer 111, a second packing layer 112 and a third packing layer 113 arranged along the height direction, and the second packing layer 112 includes the manganese-iron composite catalyst prepared in Example 1.

[0062] In the oxidation reaction device 100 of the present invention, the sewage containing bisphenol A and the solution containing persulfate flow from the first packing layer 111 of the reaction chamber to the third packing layer 113 through the second packing layer 112. Since the manganese-iron composite catalyst prepared in Example 1 is used in the second packing layer 112, the sewage containing bisphenol A and the solution containing persulfate undergo oxidation reaction in the reaction chamber. Moreover, since the metal crystals of the manganese-iron composite catalyst have a stable core-shell structure, the aggregation and peeling of metal nanoparticles can be prevented, and the service life of the manganese-iron composite catalyst is effectively extended, so that the treatment of bisphenol A in water by the persulfate advanced oxidation method can be applied on a large scale. Moreover, during the treatment process, the reaction is mild, which is conducive to energy saving. At the same time, the materials used are environmentally friendly, meet the requirements of green chemistry and sustainable development, and have broad application prospects.

[0063] In some embodiments, the first packing layer 111, the second packing layer 112 and the third packing layer 113 all include quartz sand. Using quartz sand as a component of the first packing layer 111, the second packing layer 112 and the third packing layer 113 can improve the fluid dynamics characteristics in the reaction chamber. The uniform particle size and large surface area of ​​quartz sand help to evenly distribute the fluid, reduce channelization, and improve the contact efficiency between the reactant and the manganese-iron composite catalyst. The fluid containing bisphenol A and persulfate flows through the first packing layer 111, the second packing layer 112 and the third packing layer 113 in sequence. The first packing layer 111 is conducive to removing suspended matter in the sewage before the oxidation reaction. Bisphenol A and persulfate solution undergo oxidation reaction under the catalytic action of the manganese-iron composite catalyst of the second packing layer. The third packing layer 113 is used to remove the product formed by the bisphenol A reaction, thereby improving the removal effect of pollutants such as bisphenol A in sewage.

[0064] In some embodiments, a water inlet 114 is provided at the bottom of the reaction cylinder 110, and a water outlet 115 is provided at the top of the reaction cylinder 110. The fluid containing bisphenol A and persulfate can flow out from the water inlet 114, and sequentially pass through the first packing layer 111, the second packing layer 112, and the third packing layer 113 along the height direction. In this way, on the one hand, the bisphenol A and persulfate solution can be fully oxidized, and on the other hand, the external input and output devices are used to continuously treat the sewage containing bisphenol A and improve the sewage treatment efficiency.

[0065] In some embodiments, an exhaust port 116 is provided at the top of the reaction tube 110. In this way, the gas generated during the oxidation reaction can be discharged from the exhaust port 116, thereby preventing the oxidation reaction device 100 from being damaged due to excessive pressure in the reaction chamber, which is beneficial to improving the safety of the oxidation reaction device 100.

[0066] Illustratively, in one embodiment of the present invention, the diameter of the reaction tube 110 of the oxidation reaction device 100 can be 5 cm to 10 cm, the height of the oxidation reaction device 100 can be 20 cm to 50 cm, the first packing layer 111 is filled with quartz sand, the second packing layer 112 is a mixed layer of quartz sand and manganese-iron composite catalyst, the thickness of the second packing layer 112 can be 2 cm to 5 cm, wherein the content of manganese-iron composite catalyst is 20 mg to 50 mg.

[0067] In a third aspect, an embodiment of the present invention further provides a water treatment device 200 , comprising: the above-mentioned oxidation reaction device 100 , a water tank 210 , a water pump 220 , a dosing box 230 and a dosing pump 240 .

[0068] The water tank 210 is used to supply water to the oxidation reaction device 100, the water inlet end of the water pump 220 is connected to the water tank 210, and the water outlet end is connected to the water inlet 114 of the oxidation reaction device 100. The dosing box 230 is used to provide an oxidant (such as persulfate) to the oxidation reaction device 100, the input end of the dosing pump 240 is connected to the dosing box 230, and the output end of the dosing pump 240 is connected to the oxidation reaction device 100.

[0069] The water treatment equipment 200 of the present invention inputs wastewater containing bisphenol A into the oxidation reaction device 100 through the water pump 220, and inputs an oxidant (persulfate) into the oxidation reaction device 100 through the dosing pump 240, and performs oxidation reaction treatment in the oxidation reaction device 100. Since the above-mentioned manganese-iron composite catalyst is used in the oxidation reaction device 100, the wastewater containing bisphenol A and the persulfate solution undergo oxidation reaction in the reaction chamber, and since the metal crystals of the manganese-iron composite catalyst have a stable core-shell structure, the aggregation and peeling of metal nanoparticles can be prevented, thereby effectively extending the service life of the manganese-iron composite catalyst, so that the treatment of bisphenol A in water by the persulfate advanced oxidation method can be applied on a large scale.

[0070] In a fourth aspect, an embodiment of the present invention further provides an application of treating wastewater using the water treatment device 200, which may include:

[0071] The reaction temperature is room temperature, the concentration of bisphenol A in the wastewater in the water tank 210 is 1 mg / L to 10 mg / L, the flow rate of the water pump 220 to the oxidation reaction device 100 is 50 L / d to 100 L / d, the concentration of the oxidant (persulfate) is 0.5 mol / L to 2.0 mol / L, and the flow rate of the dosing pump 240 to the oxidation reaction device 100 is 0.05 L / d to 1.00 L / d.

[0072] A specific application of the water treatment device of this embodiment is introduced below:

[0073] At room temperature, wastewater containing bisphenol A is made to flow out of the water tank 210 through the water pump 220, the concentration of bisphenol A is 5 mg / L, and the flow rate is set to 50 L / d. At the same time, a solution containing persulfate is made to flow out of the dosing tank 230 through the dosing pump 240, the concentration of persulfate is 1.0 mol / L, and the flow rate is 0.20 L / d; the aqueous solution containing bisphenol A and the oxidant solution are evenly mixed at the bottom of the oxidation reaction device 100, and continuously pass through the second packing layer 112 under the action of hydrodynamic force, and the manganese-iron composite catalyst activates a large amount of oxidizing active substances produced by persulfate, which react with bisphenol A in the water to oxidize and decompose it.

[0074] 5 ml of filtrate discharged from the oxidation reaction device 100 was collected on the 0.5 day, 1 day, 1.5 days, 2 days, 2.5 days, 3 days, 3.5 days, 4 days, 4.5 days, 5 days, 5.5 days, 6 days, 6.5 days, 7 days, 7.5 days, 8 days, 8.5 days, 9 days, 9.5 days and 10 days of the reaction, and filtered through a 0.22 μm filter to detect the bisphenol A concentration therein.

[0075] Draw a graph of pollutant concentration versus time, with time as the horizontal axis and pollutant removal efficiency as the vertical axis, see Figure 4 . During the 10-day reaction process, the pollutant degradation efficiency in the oxidation reaction device 100 remained above 90.4%, with no obvious downward trend, proving that the oxidation reaction device 100 filled with the manganese-iron composite catalyst has an extremely high instantaneous reaction efficiency. A pure quartz sand column not filled with the manganese-iron composite catalyst was used as a control group. In the control reaction device, the highest bisphenol A removal efficiency was only 12.2%, indicating that quartz sand has almost no persulfate activation ability, and the component that plays the main catalytic role in the oxidation reaction device 100 is the manganese-iron composite catalyst.

[0076] Since the manganese-iron composite catalyst has a graphene-metal particle core-shell structure, the metal components are tightly wrapped and are not easy to dissolve or escape. Therefore, the concentration of metal ions discharged from the oxidation reaction device 100 is very low. Figure 5 , indicating that the manganese-iron composite material is extremely resistant to hydraulic impact and acid, has no secondary pollution, and has a long service life. It can support long-term treatment of wastewater containing bisphenol A, reduces the frequency of catalyst replacement, and is conducive to reducing equipment costs, thereby expanding the scale of treatment of wastewater containing bisphenol A.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A manganese-iron composite catalyst, characterized in that: The invention is prepared by comprising the following raw materials: K3[Fe(CN)6], Mn(NO3)2, polyvinyl pyrrolidone and deionized water.

2. The ferromanganese composite catalyst according to claim 1, characterized in that The ratio of K3[Fe(CN)6], Mn(NO3)2 and polyvinyl pyrrolidone is: 0.005~0.015mol: 0.005~0.015mol: 1.5~5.0g: 100~500ml.

3. The ferromanganese composite catalyst according to claim 1 or 2, characterized in that The molar ratio of K3[Fe(CN)6] and Mn(NO3)2 is 0.9-1.1:0.9-1.

1.

4. The method for preparing the ferromanganese composite catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) K3[Fe(CN)6], Mn(NO3)2 and polyvinyl pyrrolidone are mixed with deionized water and stirred to obtain a precipitate; (2) washing and drying the precipitate from step (1) to obtain a ferromanganese precursor material; (3) Calcining the ferromanganese precursor material in step (2) under a N2 atmosphere to obtain a ferromanganese composite catalyst.

5. The method for preparing the ferromanganese composite catalyst according to claim 4, characterized in that: In step (1), the stirring time is 30 to 60 minutes.

6. The method for preparing the ferromanganese composite catalyst according to claim 4, characterized in that: In step (2), the drying temperature is 60 to 80° C. and the drying time is 18 to 36 hours.

7. The method for preparing the ferromanganese composite catalyst according to claim 4, characterized in that: In step (3), the calcination temperature is 600-800° C., the calcination time is 2-3 hours, and the heating rate is 5-10° C. / min.

8. An oxidation reaction device, characterized in that: It comprises a reaction cylinder, a reaction chamber is defined in the reaction cylinder, the reaction chamber has a first packing layer, a second packing layer and a third packing layer arranged from bottom to top along the height direction, the second packing layer contains the manganese-iron composite catalyst according to any one of claims 1 to 3 or the manganese-iron composite catalyst prepared by the preparation method according to any one of claims 4 to 7.

9. The oxidation reaction device according to claim 8, characterized in that: The first packing layer, the second packing layer and the third packing layer all contain quartz sand; the bottom end of the reaction cylinder is provided with a water inlet, and the top end of the reaction cylinder is provided with a water outlet and an exhaust port.

10. A water treatment device, characterized in that: It comprises a water tank, a water pump, a dosing box, a dosing pump and the oxidation reaction device according to any one of claims 8 to 9; the water tank is used to supply water to the oxidation reaction device; the water inlet end of the water pump is connected to the water tank, and the water outlet end of the water pump is connected to the water inlet of the oxidation reaction device; the dosing box is used to provide oxidant to the oxidation reaction device; the input end of the dosing pump is connected to the dosing box, and the output end of the dosing pump is connected to the oxidation reaction device.